Fechamento de diastema anterior: associação de procedimentos ortodôntico e restaurador - Ribeiro, Tiago Turri de Castro; Cunha, Leonardo Fernandes da; Modelli, José; Raveli, Dirceu Barnabé [UNESP] (My University, 2011)
Several aspects beyond the restorative phase itself such as orthodontic movement and periodontal treatment must be considered in cases of closure of diastemas. In such cases, a multidisciplinary approach is essential. As patients during orthodontic treatment may show high risk of developing dental caries and periodontal disease, inflammation of the gingival tissue is a common finding. For this reason, a preliminary basic periodontal treatment is critical to the success of restorative procedure. In addition, postoperative care and instruction in phonetics, oral hygiene and periodic control must be considered by professionals and patients. Thus, this paper demonstrates through a case report, pre and postoperative issues that should be considered during the closure of diastemas using a layering technique with resin composites

Muitas vezes, somente a mecânica ortodôntica não é suficiente para solucionar os casos de fechamento de diastemas. Da mesma forma, apenas uma abordagem restauradora pode resultar em dentes desproporcionais, com uma aparência desarmônica. Nesses casos, uma abordagem multidisciplinar é fundamental. Uma movimentação ortodôntica prévia é essencial para o sucesso do tratamento restaurador, assim como uma comunicação entre o ortodontista e o profissional que realizará as resta urações pode ser favorável no prognóstico. Portanto, esse trabalho ilustra por meio de um caso clínico, aspectos ortodônticos e restauradores que devem ser considerados na realização de fechamento de diastemas.
Anterior closure diastema: association of orthodontic and restorative procedures
Keywords: Diastema; Esthetics; Dental; Orthodontics; Esthetics dental; Diastema; Estética dentária; Ortodontia; Odontologia cosmética